Injuries in the Victorian thoroughbred racing industry. Issue 10 (14th May 2007) - Cowley, S; Bowman, B; Lawrance, M
Abstract : There is increasing concern in Australia about safety in the thoroughbred racing industry, but there has been no reported analysis of injury data. This review analyses injury and workers' compensation data recorded in Victoria. On the basis of the results, it is recommended that the injury and incident data collection systems are improved such that they are not only more complete but also accumulate more detailed information about the location of an incident or injury event, the activity at the time of the incident or injury event, and factors that may have influenced the occurrence.